Stretchable optical fibre sensor for soft surgical robot shape reconstruction - He, Yanlin; Gao, Likun; Bai, Yuchen; Zhu, Hangwei; Sun, Guangkai; Zhu, Lianqing; Xu, Haidong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
Soft robotics presents several advantages in the field of minimally invasive surgery. However, existing methods have not fully addressed problems related to soft robot shape sensing due to the complex motion of soft robots and the stretchable nature of the soft materials employed. This study demonstrates the shape sensing of a soft robot with a helically embedded stretchable fibre Bragg grating (FBG)-based optical fibre sensor. Unlike straight FBG embedding configurations, this unique helical configuration prevents sensor dislocation, supports material stretchability, and facilitates shape detection for various soft-robot movements. The proposed soft-robot design principle and FBG sensor are analysed and their fabrication process, which includes an FBG-written optical fibre sensor, is described. Bending experiments are conducted with the soft robot, the wavelengths of FBG sensors at diﬀerent bending and telescopic movement states are obtained, and the soft-robot shape is reconstructed. Experimental results demonstrate that the maximum error between FBG sensing and the actual bending state is less than 2.5%, validating the feasibility and eﬀectiveness of the proposed helical stretchable FBG sensing method for the shape measurement of soft robots. These results indicate the potential and applicability of this shape-sensing approach in biomedical research.
Optica Applicata, Vol. 51, 2021, nr 4, s. 589-604
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; soft robotics; minimally invasive surgery; shape measurement; stretchable structure; optical fibre